Diversity and association analysis in bread wheat (Triticum aestivum - Kumar, Monu; Sharma, Ram Kumar; Singh, Gyanendra Pratap; Kala, YK (Journal of Cereal Research, 2017)
The present study was undertaken to assess level of genetic diversity and inter relationship among grain yield and its components as well as some physiological characters under heat stress environment.Â Doi.org/ 10.25174/2249-4065/2017/74267.